Recurrent Melioidotic Neck Abscess - Eh Dam, V Sha Kri (Bangladesh Journal of Medical Science, 2025)
Background Melioidotic neck abscess is a rare complication of chronic infectious disease caused by Burkholderia pseudomallei. Recurrent cases with laboratory confirmation, which could be caused by incomplete eradication of infection or immunocompromised state of patient, have never been described in the literature. Its management is challenging, with no consensus to date of treatment regime. Case presentation We present a case of a young patient with multiple comorbidities presenting with recurrent melioidotic neck abscess, successfully treated with surgical drainage and a long-term combination of antibiotics. Conclusion There are wide range clinical manifestations of melioidosis with pneumonia is the most common presentation, while neck abscess is rarely reported. The bacteria may remain inactive for some time and re-activate when the host immune system has deteriorated. Fail to completely eradicate the disease may predispos to another episode of complication. Longer duration of treatment and follow-up should be considered, especially in immunocompromised patients, and the patients should be managed under multidisciplinary teams to minimize the risk of recurrent and catastrophic complications. BJMS, Vol. 24 No. 04 October’25 Page : 1341-1345